Randomized controlled trial of supportive care interventions to manage psychological distress and symptoms in Latinas with breast cancer and their informal caregivers. Issue 1 (2nd January 2020) - Badger, Terry A.; Segrin, Chris; Sikorskii, Alla; Pasvogel, Alice; Weihs, Karen; Lopez, Ana Maria; Chalasani, Pavani
Abstract: Objective: The purpose of this study was to test two 2-month psychosocial interventions (Telephone Interpersonal Counseling [TIPC] and Supportive Health Education [SHE]) to improve quality of life (QOL) outcomes for Latinas with breast cancer and their informal caregivers. Methods: Two hundred and forty-one Latinas with breast cancer and their caregivers were assessed at baseline, immediately after the 2-month intervention, at 4 and 6 months after baseline. QOL outcomes were psychological distress, symptoms and social support. Results: Linear mixed effects models showed that for cancer survivors at 2 months, TIPC produced lower adjusted mean depression scores compared to SHE. At 4 months, SHE had reduced total number of symptoms, global symptom distress, and social isolation compared to TIPC. Only total number of symptoms was lower in SHE than in TIPC at 6 months. Among caregivers at 2 months, total number of symptoms, global symptom distress, and anxiety were lower, and self-efficacy for symptom management was higher in SHE compared to TIPC. Caregiver depression was lower in TIPC compared to SHE at 4 months. Conclusions: These telephone delivered interventions improved different outcomes. TIPC demonstrated superior benefits for depression management and SHE was more successful in anxiety and cancer-related symptom management.